2015
DOI: 10.1155/2015/379538
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin Attenuates Atherogenesis through Inducing Macrophage Apoptosis via Inhibition of AKT Ser473 Phosphorylation and Downregulation of Plasminogen Activator Inhibitor-2

Abstract: Macrophage survival is believed to be a contributing factor in the development of early atherosclerotic lesions. Dysregulated apoptosis of macrophages is involved in the inflammatory process of atherogenesis. Apigenin is a flavonoid that possesses various clinically relevant properties such as anti-inflammatory, antiplatelet, and antitumor activities. Here we showed that apigenin attenuated atherogenesis in apoE −/− mice in an in vivo test. In vitro experiments suggested that apigenin induced apoptosis of oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Further studies showed that apigenin enhanced total superoxide dismutase (SOD) activity and reduced malondialdehyde (MDA) content in myocardium via repression of p38 MAPK signaling pathway, suggesting that apigenin can prevent cardiomyocytes from I/R-induced injury. Thus far, the studies regarding the athero-protective effects of apigenin and the underlying molecular mechanisms are limited to a certain extent [14,15]. Many kinds of flavonoid can exert athero-protection through regulation of lipid and cholesterol metabolism and macrophage ABCA1 expression [45][46][47], which makes us wonder whether apigenin can inhibit atherogenesis by maintaining cholesterol homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies showed that apigenin enhanced total superoxide dismutase (SOD) activity and reduced malondialdehyde (MDA) content in myocardium via repression of p38 MAPK signaling pathway, suggesting that apigenin can prevent cardiomyocytes from I/R-induced injury. Thus far, the studies regarding the athero-protective effects of apigenin and the underlying molecular mechanisms are limited to a certain extent [14,15]. Many kinds of flavonoid can exert athero-protection through regulation of lipid and cholesterol metabolism and macrophage ABCA1 expression [45][46][47], which makes us wonder whether apigenin can inhibit atherogenesis by maintaining cholesterol homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…It can prevent oxidized low-density lipoprotein (ox-LDL)-induced endothelial monocyte adhesion and improve endothelial dysfunction via inhibiting LDL oxidation and endothelial ox-LDL uptake in the early stages of AS [13]. Zeng et al revealed that apigenin attenuated atherogenesis through inducing apoptosis of ox-LDL-loaded murine peritoneal macrophages (MPMs) via down-regulation of plasminogen activator inhibitor 2 (PAI-2) in vivo [14]. Moreover, apigenin can lower the expression of pro-inflammatory cytokines and promote apoptosis of foam cells by inhibiting autophagy of foam cells during atherogenesis [15].…”
Section: Introductionmentioning
confidence: 99%
“…On the whole, the treatments existing for ischaemic injury, including myocardial infarction, are directed towards reinstatement of blood supply to cardiac tissue and put off the damage imposing at the time of injury [7]. The existing management for MI includes beta blockers, ACE inhibitors/ARBs, nitrates and anti-thrombotic agents [8]. Though, in the face of the upgrading and ease of use of these therapies, the early death rate from acute MI is about 30 %, with more than half of these deaths occurring before the stricken individual reaches the hospital [9].…”
Section: Introductionmentioning
confidence: 99%
“…The increase of E-cadherin expression induced by matrin can be attributed to the inhibition of AKT signaling [44]. Apigenin which has been mentioned before can inhibit phosphorylation of AKT Ser473 and attenuate atherogenesis through inducing macrophage apoptosis [45].…”
Section: Pi3k/akt Signaling Pathwaymentioning
confidence: 92%